Ascending Single‐Dose, Double‐Blind, Placebo‐Controlled Safety Study of Noribogaine in Opioid‐Dependent Patients. Issue 6 (1st April 2016) - Glue, Paul; Cape, Gavin; Tunnicliff, Donna; Lockhart, Michelle; Lam, Fred; Hung, Noelyn; Hung, C. Tak; Harland, Sarah; Devane, Jane; Crockett, R. S.; Howes, John; Darpo, Borje; et al.
Abstract: Ibogaine is a psychoactive substance that may reduce opioid withdrawal symptoms. This was the first clinical trial of noribogaine, ibogaine's active metabolite, in patients established on methadone opioid substitution therapy (OST). In this randomized, double‐blind, placebo‐controlled single ascending‐dose study, we evaluated the safety, tolerability, and pharmacokinetics of noribogaine in 27 patients seeking to discontinue methadone OST who had been switched to morphine during the previous week. Noribogaine doses were 60, 120, or 180 mg (n = 6/dose level) or matching placebo (n = 3/dose level). Noribogaine was well tolerated. The most frequent treatment‐emergent adverse events were noneuphoric changes in light perception ∼1 hour postdose, headache, and nausea. Noribogaine had dose‐linear increases for AUC and Cmax and was slowly eliminated (mean t1/2 range, 24–30 hours). There was a concentration‐dependent increase in QTcI (0.17 ms/ng/mL), with the largest observed mean effect of ∼16, 28, and 42 milliseconds in the 60‐, 120‐, and 180‐mg groups, respectively. Noribogaine showed a nonstatistically significant trend toward decreased total score in opioid withdrawal ratings, most notably at the 120‐mg dose; however, the study design may have confounded evaluations of time to resumption of OST. Future exposure‐controlled multiple‐dose noribogaine studies are planned that will address these safety and design issues.